Soccer kick kinematic differences between experienced and non-experienced soccer players - Muñoz López, Alejandro; González Jurado, José Antonio (FEADEF, 2012)
Purpose: to examine kinematic differences of instep soccer kick between experienced and non-experienced soccer players. Subjects: 17 men between 17 and 21 years old. Methodology: a 3D film system with 4 cameras was used. Maximum power instep kicks were executed. It was analyzed feet velocity in the impact, maximum hip extension, maximum knee flexion and kick phases duration. Results: were found significant differences in feet velocity with non-dominant leg in the impact moment (m/s) (Experienced: 14.5±.52, Non-experienced: 12.5±.5; p<.001) and maximum hip extension (degrees) (Experienced: 39.2 ± 1.3, Non-experienced: 34.28±3.2; p<.001). Also were significant differences in the second phase duration in both legs (p<.05). Conclusions: Maximum instep soccer kick show significant differences between groups of different level only in non-dominant leg.